2016
DOI: 10.1111/jog.13114
|View full text |Cite
|
Sign up to set email alerts
|

Normogram of umbilical artery Doppler indices in singleton pregnancies in south‐western Nigerian women

Abstract: A normogram of umbilical artery Doppler indices was constructed, which showed that the indices decreased with gestational age. These normative data could serve as reference ranges for evaluation of the umbilical artery circulation in this locality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 21 publications
1
21
0
Order By: Relevance
“…The highest prevalence was reported by Yoon et al, who reported a prevalence of AEDF or REDF of 2.13% amongst 328 unselected-risk women in South Korea [38]. The four studies (898 women) conducted in lower middle-income countries (Bangladesh, Papua New Guinea, Nigeria and Tunisia) did not report any cases of AEDF or REDF [39][40][41][42]. Similarly, a three-country prospective cohort study of 431 healthy, low-risk women by Drukker et al in Brazil, Kenya and the UK identified no AEDF cases in any country [29].…”
Section: Resultsmentioning
confidence: 92%
“…The highest prevalence was reported by Yoon et al, who reported a prevalence of AEDF or REDF of 2.13% amongst 328 unselected-risk women in South Korea [38]. The four studies (898 women) conducted in lower middle-income countries (Bangladesh, Papua New Guinea, Nigeria and Tunisia) did not report any cases of AEDF or REDF [39][40][41][42]. Similarly, a three-country prospective cohort study of 431 healthy, low-risk women by Drukker et al in Brazil, Kenya and the UK identified no AEDF cases in any country [29].…”
Section: Resultsmentioning
confidence: 92%
“…We found only five articles presenting reference ranges for CPR. Table 1 describes the main characteristics and number of citations of the 19 selected studies [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] .…”
Section: Resultsmentioning
confidence: 99%
“…We found important sources of bias in the most widely used studies 18 ; ultrasound examinations were not performed for research purposes 24,25,28,30,33,34,40 , neither the recruitment period 24,25,[27][28][29]31,32,34,38 nor perinatal results 24 were described, or the study was performed at a single center [24][25][26][27][28][29][30][31]37,39 . We also found a lack of reporting of necessary sample sizes 24,26,[28][29][30][31][34][35][36]38,40 , gestational-age dating method [25][26][27][28]31,40 , experience of the sonographers 24,[26][27][28]…”
Section: This Is the First Systematic Review To Analyze The Impact Ofmentioning
confidence: 99%
“…Although fixed reference points such as the fetal or placental end of the umbilical cord have been previously used for Doppler velocimetry, free‐floating loops of umbilical cord (as used in the present study) have remained popular due to the ease with which they can be identified 31 . In a previous study conducted at the current study institution with similar objectives, 32 a cross‐sectional methodology was used, whereby each fetus was sampled once without a rigorous technique of pregnancy dating. In addition, that study did not report the outcomes of the pregnancies.…”
Section: Discussionmentioning
confidence: 99%